2020
DOI: 10.1101/2020.10.22.351205
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The main activatory and tension-sensitive transitions occur within Prozac sensitive down-states of the potassium selective TREK-2 channel

Abstract: The two-pore domain potassium selective (K2P) ion-channels TREK-1, TREK-2, and TRAAK essential mechanical stimulation sensors, and TREK-1/2 also targets for the antidepressant Nor-fluoxetine (Prozac). They respond directly to membrane tension by moving from the down to up conformation, a transition that is associated with a rise in open-probability. However, the mechanosensitive K2P (mK2P) channels can also open while occupying the down conformation, and although these channels are mostly closed, all structura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Notably, some evidence suggests that the physical basis for distinct modes of TRAAK activity shown here could be shared among K2P channels. Differences between basal and stimulus-activated openings, including their kinetics and voltage dependence (Schewe et al, 2016), have been reported for other K2Ps, suggesting that physically distinct open states could similarly underlie different modes of channel activity (Bang et al, 2000;Gnatenco et al, 2002;Kang et al, 2005;Maingret et al, 1999;Clausen et al 2020;Sorum et al, 2021). Mutations analogous to TRAAK G158D were found to activate all K2P channels, with the extent of activation correlated with the polarity of the introduced amino acid change (Ben Soussia et al, 2019).…”
Section: An Integrated Structural and Functional Model For Traak Gatingmentioning
confidence: 77%
See 1 more Smart Citation
“…Notably, some evidence suggests that the physical basis for distinct modes of TRAAK activity shown here could be shared among K2P channels. Differences between basal and stimulus-activated openings, including their kinetics and voltage dependence (Schewe et al, 2016), have been reported for other K2Ps, suggesting that physically distinct open states could similarly underlie different modes of channel activity (Bang et al, 2000;Gnatenco et al, 2002;Kang et al, 2005;Maingret et al, 1999;Clausen et al 2020;Sorum et al, 2021). Mutations analogous to TRAAK G158D were found to activate all K2P channels, with the extent of activation correlated with the polarity of the introduced amino acid change (Ben Soussia et al, 2019).…”
Section: An Integrated Structural and Functional Model For Traak Gatingmentioning
confidence: 77%
“…Notably, single channel recordings of TRAAK, and the closely related mechanosensitive K2P channels TREK1 and TREK2, suggest the presence of multiple distinct open and closed states (Bang et al, 2000;Kang et al, 2005;Maingret et al, 1999;Patel et al, 1998;Sorum et al, 2021;Xian Tao Li et al, 2006;Clausen et al 2020). In addition, alternative models for gating mechanosensitive K2Ps posit closures involving C-type gating at the selectivity filter (Chatelain et al, 2012;González et al, 2013;Li et al, 2020;Lolicato et al, 2020;Schewe et al, 2016), closures involving dewetting of the channel cavity (Aryal et al, 2014(Aryal et al, , 2015, and openings that do not involve upward movement of TM4 (Lolicato et al, 2014).…”
Section: Introductionmentioning
confidence: 99%